Pengaruh Pengembangan Karier dan Keterikatan Karyawan terhadap Kinerja Pekerja Paruh Waktu Generasi Z di Surakarta - Nathasya Niluh Asila Wulandari; Luluk Aprilia; Riris Widiyaningrum (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The increasingly complex dynamics of the workplace require organizations to optimize factors that can enhance employee performance, including among Generation Z part-time workers, who have different characteristics and work expectations compared to previous generations. This study aims to analyze the influence of career development and employee engagement on the performance of Generation Z part-time workers in Surakarta. The study employed a quantitative approach with a causal-associative design. A total of 85 respondents were selected using purposive sampling, while data were collected via a Likert-scale questionnaire and analyzed using IBM SPSS Statistics through validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results of the analysis indicate that career development has a positive and significant effect on worker performance (t = 2.577; p = 0.012), as does employee engagement, which also exerts a positive and significant influence (t = 4.761; p = 0.000). The coefficient of determination (R²) of 44.1% indicates that these two variables account for the variation in the performance of Generation Z part-time workers in Surakarta, while the remaining 55.9% is influenced by other factors outside the research model. These findings confirm that targeted career development strategies and strengthening employee engagement are crucial aspects in improving the performance of Generation Z part-time workers.